What Should Students Pay for University Course Readings? An Empirical, Economic, and Legal Analysis - Willinsky, John; Baron, Catherine (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2021)
The digital transformation of knowledge dissemination and academic publishing have sparked copyright disputes in the educational sector related to the scope of fair dealing. This study contributes (a) an empirical basis for such discussions by analyzing 3,391 course syllabuses (2015–2020) from 34 Canadian universities, and (b) a potential resolution to the disputes to which this analysis is applied. Among the reading types, 26.6% of the syllabuses had readings from academic sources, while 8.3% of the syllabuses had media articles and trade book chapters (with some overlap). The syllabus data are used to calculate a per-page royalty charge, which is used to demonstrate a proposed three-step syllabus rule to avoid double-chargingstudents for academic materials (amounting to 90.1% of readings by pages), while fairly compensating professional authors and their publishers (9.9% of readings by pages). The three-step syllabus rule provides a sound rationale for charging each student $1.40 per year to cover royalty charges for readings assigned in Canadian university courses.